Sub-agent New SIM Registration System M (EASIM) - Ting, Evelyn Li Yung (Universiti Malaysia Sarawak (UNIMAS), 2019)
The rapid growth of technology applications in today world, mobile phone has become an indispensable part of our daily lives. It allows people to communicate without any physical barriers and it leading to the amount of mobile phone user increasing rapidly. With the increase the amount of mobile phone user, the number of mobile network operator has spiraled up. There are many mobile network operators in Malaysia such Digi, Celcom, Maxis, XOX and others. With the high demand of market, the mobile network operator tends to recruit business partner who also known as sub-agent to expand their business. The main reason Sub-agent New SIM Registration System approach used is because this system allow sub-agent register new SIM for different mobile network operator in a platform. The system also provide sub-agent to view the sales report by daily, monthly and yearly. Furthermore, sub-agent also can view the customer registration status through this system. The system can be enhanced further in future so that the Sub-agent New SIM Registration System can provide more efficiency registration service to customer.